Blackness as a question of freedom: racial blackness in South African emancipatory thought - Nkopo, Athinangamso (African Studies, 2023)
This dissertation, using the theoretical framework of Afropessimism, discusses how Blackness is an ethico-political structure, in which the slave's natal alienation and social death establishes the resilient forms of Black (non)being. This project centrally argues against locating a theory of the production of Blackness in the socio-political relations of colonial subjugation, and instead proposes that Blackness is a structure, an ‘abstract code', that must be understood as deriving from racial slavery. This thought enterprise is explored in relation to South African histories of slavery to re-claim the concept of “social death” as inaugurating the structure of Blackness in Southern Africa. By suggesting how it is the absolute negation of the Black slave that creates the conditions for the possibility of the political, ethical, and civil subject – indeed, the very possibility of the Human, this study presents a discussion on how Black studies requires both a temporal and geographical reconstruction in understanding – firstly by extending much further ‘back' than the moment of South African colonialism, and secondly, by expanding the geographies of Blackness beyond European colonial rule. Furthermore, this study explores and exposes the limits of several major South African forms of political and philosophical thought and campaigns for Black emancipation: feminism, liberalism, Marxism, and Black Consciousness. An exploration which serves to highlight how the existing historiography of South Africa has disarticulated the conceptual significance of racial slavery to the making of Blackness in a way that locates it specifically in social death, with all its implications for Black (non)being. While recognizing that the political structure of Blackness precedes or cannot be located in the mechanics of South African colonial settlements, this dissertation exposes the limits and failures of a civil politics of Blackness in both national liberation and ‘progressive' struggles.